Social-Ecological Analysis of the Factors Influencing Shanghai Adolescents’ Table Tennis Skills: A Cross-Sectional Study - Xiao, Yi; Huang, Wenwen; Lu, Miaomiao; Ren, Xiaoling; Zhang, Pei (Frontiers in Psychology, 2020)
The main purpose of this study was to explore the factors that affect adolescents’ table tennis skills (ATTS) among adolescents in Shanghai from the social ecological perspective, including individual factors, social support, and physical environment. 1,526 students from Shanghai primary and secondary schools were included in this study (age = 12.31 ± 1.32 years). Participants completed a questionnaire based on social ecological theory after taking the ATTS test. A structural equation model was applied to test the relationships among the study variables. The relationship model incorporating individual factors, social support, physical environment, and ATTS test score fit the data well (χ2 = 1415.754, χ2/df = 4.96, p < 0.001; CFI = 0.914; IFI = 0.930; NFI = 0.921; RMSEA = 0.032). The investigation results showed that social support and physical environment promote adolescents’ scores on the ATTS test. At all levels of social ecology, individual factors were the most important factors for the improvement of ATTS. The level impacting most significantly on ATTS was individual factors, followed by social support, and, finally, the physical environment. Therefore, cultivating intrinsic interest is an important way to facilitate the continuous activities of adolescents. In addition, friends should support each other, and parents should give adolescents appropriate encouragement regarding table tennis exercise. Schools should provide more table tennis facilities. PE teachers should respect adolescents’ ideas, listen to students’ opinions, and encourage them to participate in table tennis training.